Kepulihan al-Halu‘ berasaskan maqamat Abu Talib al-Makki (W.386H) / Sharifah Basirah Syed Muhsin - Sharifah Basirah, Syed Muhsin (2017)
Al-halu‘ or in psychological term is known as anxiety disorder is a form of mental or psychological illness that become so prevalent in today society. This multi-dimensional phenomenon certainly has a strong influence on quality of one’s life. Islamic psychology point of view defined al-halu‘ as a mental illness that has close relationship with a pattern of human spiritual development. Therefore, a fellow Muslim should be concerned about the spiritual and mental development so that they live in a peacefulness and safe from such psychological disorders by studying, practicing and implementing method of therapy to treat and recover the disease. Therefore, in order to enrich the literature in Islamic psychotherapy, a study has been done to develop the model and modules of therapy based on Sufism, especially on the nine maqamat as proposed by a well-known Sufi figure, Shaykh Abu Talib al-Makki (d. 386H / 966M) in his magnum opus Qut al-Qulub called Psychotherapy Model of al-Makki (MPM). The study also aimed to evaluate the effectiveness and reliability of Psychotherapy Model of al-Makki and its’ module in treating al-halu‘ by testing it onto the research subjects whom were diagnosed with al-halu‘ in twelve sessions of intervention and rehabilitation. The study employed a combination of technical approaches that involve qualitative and quantitative research methods comprising of review on literature related materials, interviews, observation as well as questionnaires. Data obtained from the literature review, interviews and observations were then analysed with NVivo 11, whereas data from the questionnaires were analysed with SPSS 24. Overall, this study found that Psychotherapy Model of al-Makki (MPM) and its’ module which was developed based on Abu Talib al-Makki’s elements of maqamat had demonstrated positive impacts on the subject of study and be able to also serve as a guidance to foster opportunities, enthusiasm, motivation and encouragement in their efforts to treat al-halu‘. Thus, this study had proven that Psychotherapy Model of al-Makki (MPM) and its’ module is competent in treating al-halu‘ (anxiety disorder).